2020
DOI: 10.47836/pjssh.28.4.14
|View full text |Cite
|
Sign up to set email alerts
|

Does Gender Difference Matter in Job Satisfaction? A Case of Academicians in Karnataka

Abstract: Learning organizations are the hubs of knowledge generation and dissemination. Academicians need organizational support to accomplish these time-consuming tasks effectively. The academician, when satisfied with his or her own work, is committed to the organization and demonstrates higher work productivity and work quality. The present study, with a cross-sectional design, was aimed to assess the level of job satisfaction (gender-wise) and its determinants, among academicians, in the institutions of higher educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Lecturers have families and other commitments they will have to attend to outside the workplace and the suggested solution is that the university should have a flexible schedule so that they are able to attend to other commitments. This is also consistent with the fact that when lecturers have flexible working hours, they are free to attend to other commitments and come back stressfree at work (Rahman et al, 2020). That also results in a lecturer having a full life, not all consumed by university duties and responsibilities.…”
Section: And Best Brains Have Expectations the Expectation Of Promoti...supporting
confidence: 77%
See 1 more Smart Citation
“…Lecturers have families and other commitments they will have to attend to outside the workplace and the suggested solution is that the university should have a flexible schedule so that they are able to attend to other commitments. This is also consistent with the fact that when lecturers have flexible working hours, they are free to attend to other commitments and come back stressfree at work (Rahman et al, 2020). That also results in a lecturer having a full life, not all consumed by university duties and responsibilities.…”
Section: And Best Brains Have Expectations the Expectation Of Promoti...supporting
confidence: 77%
“…This could be the case with lecturers who work 24/7 since some take their laptops home and attend to emails and other duties and responsibilities. The flexible work arrangements allow for the two different employees' needs to be catered for and when that is done leads to job satisfaction, then it is good for the university (Rahman et al, 2020). Hence, it has been mentioned that if lecturers are allowed to work from home and only go to campus whenever there is a need then they will be in a much better space to balance work and family life.…”
Section: And Best Brains Have Expectations the Expectation Of Promoti...mentioning
confidence: 99%
“…Ultimately, the quality of work produced by the lecturers will deteriorate if one or even more lecturers lose interest in their jobs. Sometimes, lecturers lose interest in their work because they are not given an opportunity to teach in the area of specialisation of their choice (Mayya et al, 2020). Interest in the work that one does plays a major role.…”
Section: Objective 2 Theme 2: Loss Of Interest At Workmentioning
confidence: 99%
“…It was shown that lecturers lose interest in work because of their environment, in this case, the rural community in which the university is situated. In addition, when lecturers do not form part of the decision-making team, it discourages them from voicing their opinions, and as it continues, they lose interest in work (Mayya et al, 2020). Therefore, loss of interest at work can cause the lecturer to look for greener pastures elsewhere.…”
Section: Objective 2 Theme 2: Loss Of Interest At Workmentioning
confidence: 99%